Analisis Strategi Pemasaran Yang Dilakukan Oleh Usaha Cemilan Dgilangemil - Nurfadillah Najwa Faraiddin; Zuhrinal M. Nawawi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Marketing strategy is a very important thing for a company to do to develop and improve the quality of its products. This strategy can be carried out by any business, be it a large business, medium business, small business or micro business. In this research the author gave the title 'Analysis of Marketing Strategies Carried Out by Small Businesses'. The purpose of this research is to provide information to readers or entrepreneurs regarding the marketing strategies carried out by the Dgilangemil business. From the research, readers and entrepreneurs can take examples of what the Dgilangemil small business did in developing their business which they started from zero until their business began to be known by many people using the marketing strategy of SWOT Analysis and Marketing Mix. In this research the author used a qualitative descriptive research method. Qualitative research is a research process carried out by observing and investigating a phenomenon that occurs and producing descriptive data. In this research, the author conducted observations, interviews and documentation with the owner of this business, namely Dea Puspita, which was carried out on December 11 2023 at the production site in the city of Langkat.